The Correlation Between Limited Range of Movement And Functional Ability of Frozen Shoulder Patient at Medical Rehabilitation Department RSUPDr Mohammad Hoesin Palembang - Ine Santia; Nyimas Fatimah; Tri Suciati (Majalah Kedokteran Sriwijaya, 2019)
Frozen shoulder is the inflammation of shoulder joint,  marked by a painful, adhesive, atrophic and shortened joint capsule. As a result, movement range of the joint becomes limited. In frozen shoulder patients, the limitation can affect and lessen functional ability. Therefore, this study is aimed to analyze the correlation between the limited range of movement of shoulder joint and the functional ability of frozen shoulder patients in Department of Medical Rehabilitation of RSUP Dr. Mohammad Hoesin Palembang.  This study is an observational analysis using correlation test with cross-sectional design. Twenty nine frozen shoulder patients in Department of Medical Rehabilitation of RSUP Dr. Mohammad Hoesin Palembang in November 2018 that met the inclusion criteria were taken as subjects of this study by using consecutive sampling technique. Functional ability was assessed with quickDASH questionnaire while shoulder joint range of movement with goniometry. Data analysis was conducted subsequent to the assessments. The result of correlation test between functional ability and shoulder joint range of movement is significant. The study findings include active flexion (p=0,000; r=-0,669), active extension (p=0,004; r=-0,520), active abduction (p=0,000; r=-0,663), active adduction (p=0,022; r=-0,423), passive flexion (p=0,001; r=-0,589), extension passive (p=0,002; r=-0,543), passive abduction (p=0,000; r=-0,676) and passive adduction (p=0,038; r=-0,388).There is a significant correlation between limited range of movement and functional ability in frozen shoulder patients from Department of Medical Rehabilitation of RSUP Dr. Mohammad Hoesin Palembang.